Fabrication of C/C–SiC–ZrB2 Ultra-High Temperature Composites through Liquid–Solid Chemical Reaction - Qian Sun (MDPI AG, 2021)
In this paper, we aimed to improve the oxidation and ablation resistance of carbon fiber-reinforced carbon (CFC) composites at temperatures above 2000 °C. C/C–SiC–ZrB2 ultra-high temperature ceramic composites were fabricated through a complicated liquid–solid reactive process combining slurry infiltration (SI) and reactive melt infiltration (RMI). A liquid Si–Zr10 eutectic alloy was introduced, at 1600 °C, into porous CFC composites containing two kinds of boride particles (B4C and ZrB2, respectively) to form a SiC–ZrB2 matrix. The effects and mechanism of the introduced B4C and ZrB2 particles on the formation reaction and microstructure of the final C/C–SiC–ZrB2 composites were investigated in detail. It was found that the composite obtained from a C/C–B4C preform displayed a porous and loose structure, and the formed SiC–ZrB2 matrix distributed heterogeneously in the composite due to the asynchronous generation of the SiC and ZrB2 ceramics. However, the C/C–SiC–ZrB2 composite, prepared from a C/C–ZrB2 preform, showed a very dense matrix between the fiber bundles, and elongated plate-like ZrB2 ceramics appeared in the matrix, which were derived from the dissolution–diffusion–precipitation mechanism of the ZrB2 clusters. The latter composite exhibited a relatively higher ZrB2 content (9.51%) and bulk density (2.82 g/cm3), along with lower open porosity (3.43%), which endowed this novel composite with good mechanical properties, including pseudo-plastic fracture behavior.